A Retrospective analysis of malaria prevalence from 2015 to 2020 in Sibu Sire Woreda, East Wollega Zone, and Western Ethiopia, - Desalegn Amenu; Temesgen Tafesse (Hasanuddin University, 2022)
The main objective of the study was to analysis the trends of malaria prevalence and surveillance data from 2015 to 2020 in Sibu Sire Woreda, East Wollega Zone, and Western Ethiopia. A Retrospective study was conducted on purposely selected hospital and health centers of Sibu sire woreda, East wollega zone zones September 2015 to August 2020. From the total 20,030 cases of malaria reported in Sibu Sire Woreda from 2015- 2020, 6,965 confirmed cases were reported, 2,234, 3,203 and 1,528 in Chingi health center, Sibu Sire health center and Sibu Sire Hospital, respectively. The high prevalence of malaria cases in the study are was reported both in autumn and spring seasons (April to September), and in relation to year distribution, more confirmed cases were reported during 2011 and 2012. The study demonstrated that malaria is a public health concern, in which P. falciparum and P. vivax are the predominant species, so, it needs more interventions to interrupt disease transmission and eventual reduction malaria of malaria cases Sibu Sire Woreda.